Merging Qualitative Design Methods With Design Science - Muhammad Afif Fathullah; Anusuyah Subbarao; Abdulaziz Ahmad; Saravanan Muthaiyah (International Journal of Qualitative Methods)
Qualitative design is a research approach to explore a central phenomenon by reporting how people see the world. Meanwhile, design science research (DSR) is a problem-solving design paradigm that seeks to enhance human knowledge via developing innovative artefacts. Qualitative design has mostly been used as an approach to finding and analysing the cause and effect of a phenomena. However, with the increasing importance of digital technology in the current digital age, research that encompasses qualitative design and developmental methods such as DSR is becoming more important. This study presents how qualitative design methods can be merged with DSR. This study will discuss how DSR research can be designed using the DSR framework and DSR process. The DSR consideration that needs to be considered when conducting DSR research will also be presented. The results show that by constructing the DSR framework and DSR process mindfully, DSR research can comply with the DSR considerations. The intersection of qualitative design and DSR approach is also presented which shows how using these two approaches can align more with the current digital age. We have then constructed a DSR framework and process that incorporates qualitative design methods. We hope that the results and presentation of this study will be able to help researchers who are interested in doing DSR research that merges qualitative design methods to know how to comply with DSR considerations and how to incorporate them into DSR research.